New Media and the Rise of Citizen Journalism - Ololo Stephanie Ola (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2026)
The emergence of new media has significantly transformed the landscape of journalism and public communication across the world. With the rise of digital technologies, social networking sites, blogs, online forums, and mobile communication devices, ordinary citizens now play active roles in gathering, producing, and disseminating news. This development has given birth to citizen journalism, a form of journalistic practice in which non-professionals participate directly in the reporting of events and issues affecting society. Unlike traditional journalism, which is often controlled by professional gatekeepers and institutional routines, citizen journalism thrives on immediacy, accessibility, interactivity, and user-generated content. The paper adopted quantitative method using survey and questionnaire was used as an instrument of data collection. This paper examines how new media has facilitated the growth of citizen journalism, its contributions to democratic participation, information sharing, and social accountability, as well as the challenges associated with misinformation, lack of professionalism, ethical concerns, and weak regulatory mechanisms. The study argues that while citizen journalism has expanded the frontiers of freedom of expression and diversified news production, it also raises critical questions about credibility, verification, and responsibility in the digital age. The paper concludes that citizen journalism has grown considerably in Nigeria due to the widespread availability of digital technologies and social media platforms. These tools have enabled ordinary citizens to participate actively in news reporting, public debate, and civic engagement.